Microwave circuit theory and foundations of microwave metrology - Engen, Glenn F. (Institution of Engineering and Technology, 1992)
Starting with the field of equations, the book first outlines the theoretical basis for microwave circuit theory with particular emphasis on its similarity to, and difference from, the low frequency counterpart. This leads to an identification of parameters to be measured and is followed by a survey of measurement methods with the emphasis on the 'why' in addition to 'how'. Special emphasis is given to 'power equation method', adapter evaluation, the six-port network analyser and noise. In these areas in particular, the book includes recently developed material that has not been previously published.